PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN DESA WISATA DI DESA KALIGONO KECAMATAN KALIGESING KABUPATEN PURWOREJO - Muhammad Mukhib Mubarok; Nina Widowati; Teuku Afrizal (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Community empowerment places the community as a subject not an object so as to create an independent society. This study aims to find out about the Stages of Community Empowerment through Tourism Village Development in Kaligono Village, Kaligesing District, Purworejo Regency. This research is a qualitative descriptive research with data collection through observation, interviews, documentation, and literature study. This study uses purposive and accidental techniques. This study uses the theory of stages of community empowerment to examine and identify supporting and inhibiting aspects of community empowerment through the development of a tourist village in Kaligono Village. The results of this study indicate that the process of community empowerment through the development of a tourist village goes through 4 stages, namely the location/region selection stage, the socialization stage, the program implementation stage, and the evaluation stage. The results of the research show that in the selection stage of the location/area of community empowerment and the socialization stage there were no obstacles, but there were obstacles in the program implementation stage and the evaluation stage so that community empowerment through the development of a tourist village in Kaligono Village was not optimal which can be seen from the lack of maintenance of tourist object facilities and environmental conditions of tourist objects that are less clean due to limited funds to carry out maintenance of tourist objects, the level of participation of the community who are members of the management of POKDARWIS and BPDW has decreased both in number and activity, promotions carried out have not been maximized, community activities for entrepreneurship are still low, and there is no follow-up of the evaluation results and the absence of innovations made to encourage the development of the Kaligono Tourism Village. The suggestions recommended by the researchers are to allocate village funds for tourism object maintenance activities, carry out activities that can encourage the community to increase entrepreneurial activity, regenerate POKDARWIS and BPDW management, follow up on evaluation results and carry out innovations to support the development of the Kaligono Tourism Village.